Waste Composting to Manage Household Waste: Pengomposan Sampah untuk Mengelola Sampah Rumah Tangga - Budi Yulianto; Aries Prasetyo; Handoyo; Nurlailis Saadah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Waste management is a problem that occurs in several places including orphanages. This must be handled properly. PSBM (Community-Based Waste Management) is the right alternative so that the waste problem is handled properly and correctly so that it does not cause danger and disease that occurs due to unpleasant odors and disturbs the community. Composting is waste management by making compost using either chemical or natural materials. Community service activities at this orphanage use methods that emphasize community involvement and provide education through counseling or campaigns about the dangers and benefits of waste. Activities are also carried out through waste sorting and composting training using simple materials and tools. The results of the activities show that there is an increase in the understanding and skills of orphanage residents in utilizing household waste into compost (waste composting). Orphanage residents have sorted organic and inorganic waste using closed trash bins and have a special place for composting waste in each house. This community service activity is very beneficial for the surrounding environment which becomes clean, healthy and gets plant fertilizer.